Attenuation of fear‐conditioned analgesia in rats by monoacylglycerol lipase inhibition in the anterior cingulate cortex: Potential role for CB2 receptors. (12th February 2020) - Corcoran, Louise; Mattimoe, Darragh; Roche, Michelle; Finn, David P.
Abstract : Background and Purpose: Improved understanding of brain mechanisms regulating endogenous analgesia is important from a fundamental physiological perspective and for identification of novel therapeutic strategies for pain. The endocannabinoid system plays a key role in stress‐induced analgesia, including fear‐conditioned analgesia (FCA), a potent form of endogenous analgesia. Here, we studied the role of the endocannabinoid 2‐arachidonoyl glycerol (2‐AG) within the anterior cingulate cortex (ACC; a brain region implicated in the affective component of pain) in FCA in rats. Experimental Approach: FCA was modelled in male Lister‐hooded rats by assessing formalin‐evoked nociceptive behaviour in an arena previously paired with footshock. The effects of intra‐ACC administration of MJN110 (inhibitor of monoacylglycerol lipase [MGL], the primary enzyme catabolizing 2‐AG), AM630 (CB2 receptor antagonist), AM251 (CB1 receptor antagonist) or MJN110 + AM630 on FCA were assessed. Key Results: MJN110 attenuated FCA when microinjected into the ACC, an effect associated with increased levels of 2‐AG in the ACC. This effect of MJN110 on FCA was unaltered by co‐administration of AM251 but was blocked by AM630, which alone reduced nociceptive behaviour in non‐fear‐conditioned rats. RT‐qPCR confirmed that mRNA encoding CB1 and CB2 receptors was detectable in the ACC of formalin‐injected rats and unchanged in those expressing FCA. Conclusion and Implications: These results suggest that an MGL substrate in the ACC, likely 2‐AG, modulates FCA and that within the ACC, 2‐AG‐CB2 receptor signalling may suppress this form of endogenous analgesia. These results may facilitate increased understanding and improved treatment of pain‐ and fear‐related disorders and their co‐morbidity.